The Role of Google Educational Tools in Enhancing and Developing the Professional Competencies of English Language Teachers - Amal Sabbar Julaid (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study explores the impact of using Google educational applications on enhancing the skills of English language teachers. To achieve this, a quasi-experimental design was employed with two groups: experimental and control, comprising 90 participants. Data were collected through preand post-tests. The results, analyzed using a t-test, revealed the following: ➢ There were significant differences in the mean scores of the four basic language skills, with the experimental group outperforming the control group in reading. ➢ No significant differences were found between male and female participants in the experimental group using Google applications. Effect size calculations indicated that Google applications improved English teaching skills by 36%. Specifically, reading improved by 28%, writing by 30%, and grammar by 44%.